PROFESIONALITAS KEPALA SEKOLAH: Analisis Antara Idealita dan Realita - Sitti Mania (Faculty of Tarbiyah and Teacher Training Universitas Islam Negeri Alauddin Makassar, 2011)
A head master as a top leader of a school is responsible for a hard job and determines the future of the school. The head master should have three important skills; they are technical competence re-lated to specific skills for running operational activities of as a head master. The second is interpersonal competence; this is a skill to work with others and to motivate teachers and other subordinates. Finally, conceptual competence; this is about the head master’s ability to pro-duce concept, to analyse and solve problems of schools. Despite this, a number of headmasters cannot run their daily activities as it should be due to a number of factors. This paper discusses a number of ways to overcome such issue.